1997
DOI: 10.1021/es970375t
|View full text |Cite
|
Sign up to set email alerts
|

Polychlorinated Biphenyls in Arctic Air. 1. Temporal and Spatial Trends:  1992−1994

Abstract: In 1992, a long term program was established to measure the airborne concentrations of persistent organic pollutants (POPs) in the Arctic. To maximize spatial variation over a wide geographical area, three Arctic locations were selected; two sites in Canada, Alert on Ellesmere Island and Tagish in the western Yukon, and one in Russia at Dunai Island in eastern Siberia. PCB data is presented here for the years 1992-1994. Mean ∑PCB concentrations for 1993, the year when all three sites were running simultaneousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
78
0
6

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(101 citation statements)
references
References 23 publications
(35 reference statements)
17
78
0
6
Order By: Relevance
“…1). Tri-CBs dominated the homolog pattern, in agreement with those reported in the literature (Stern et al 1997;Choi et al 2008). Fractions of tri-, tetra-, penta, hexa-, hepta-, and octa-CBs in ∑ 32 PCBs were 52.6, 23.2, 14.2, 8.1, 1.7, and 0.2 %, respectively.…”
Section: Pcbssupporting
confidence: 92%
See 1 more Smart Citation
“…1). Tri-CBs dominated the homolog pattern, in agreement with those reported in the literature (Stern et al 1997;Choi et al 2008). Fractions of tri-, tetra-, penta, hexa-, hepta-, and octa-CBs in ∑ 32 PCBs were 52.6, 23.2, 14.2, 8.1, 1.7, and 0.2 %, respectively.…”
Section: Pcbssupporting
confidence: 92%
“…In Europe (EU-28), PAH levels have been declining from 1990 until ≈2002 but were leveling off, even slightly increasing thereafter (EEA 2014). PCB levels in air are believed to slowly fall in all regions (except in the Arctic; Lammel and Stemmler 2012), which is confirmed for central Europe for 1997(Dvorská et al 2009), but it could be regionally overcompensated by climate variability (mobilization from ground compartments triggered by higher temperatures; Lamon et al 2009). The decision about the prohibition of PCB usage in Turkey was published in the official gazette in 1993, then entered into force in 1996 (RCHC 1993), but the long-term PCB trend in Turkey is not confirmed.…”
Section: Exposure and Risk Assessmentmentioning
confidence: 93%
“…Tomy et al (32) have shown that PFOS biomagnifies in the arctic marine food chain. As atmospheric circulation and ocean currents are currently thought to be responsible for the distribution of PCBs (24,25,33), this supports an atmospheric and oceanic distribution model for PFAs and/or their precursors. …”
Section: Concentrationsupporting
confidence: 63%
“…The relative significance of local versus more distant sources of contamination in the Arctic has been the source of some debate in the literature Norstrom and Muir, 1994;Stern et al, 1997;Braune et al, 1999). While long-range transport of organic contaminants is well known and understood, local source redistribution is less well documented and accepted.…”
Section: Introductionmentioning
confidence: 99%